A randomized trial to evaluate the use of text messaging, letter, and telephone call reminders to improve return of blood donors with reactive serologic tests. Issue 1 (23rd October 2016) - Porto‐Ferreira, Francisco Augusto; de Almeida‐Neto, Cesar; Murphy, Edward L.; Montebello, Sandra de Camargo; Nogueira, Fátima Aparecida Hangai; Koga da Silva, Edina Mariko; MacFarland, William; Custer, Brian
Abstract : BACKGROUND: Low return rates for notification and counseling among donors with reactive serologic screening tests have been reported worldwide. A randomized trial to test the effectiveness of text message, letter, or telephone call reminders to improve return among nonresponding first‐time blood donors with reactive serologic tests was conducted. STUDY DESIGN AND METHODS: Donors with serologically reactive screening test results who had a cell phone and resided in the metropolitan telephone area code of São Paulo in the period from August 2013 through July 2014 were eligible. A consecutive sample of first‐time donors with reactive screening tests who had not responded to a standard letter requesting the donor return to the blood center were randomly assigned to receive a text, a new letter, or a telephone call requesting return for notification and counseling. Return rates were measured over the subsequent 30 days. RESULTS: The return rate after a phone call reminder was better than that for a text message (39.8% vs. 28.4%; odds ratio [OR], 1.66; 95% confidence interval [CI], 1.05‐2.64) but not better than that for a letter (39.8% vs. 34.4%; OR, 1.26; 95% CI, 0.80‐1.99). Older age was a predictor of higher rate of return with each year increase in age associated with a 2% increase in the odds of return (OR, 1.02; 95% CI, 1.01‐1.04). CONCLUSION: In nonresponding serologic reactive donors, telephone call led to a higher return rate than text message. The results of this study suggest that use of text messages, while attractive for its simplicity, will not lead to increased donor notification success after serologically reactive marker results from blood donation in Brazil.